NOCHIZIQLI TENGLAMALARNI YECHISHDA NYUTON VA STEFFENSEN USULLARINING SAMARADORLIGINI ANIQLASH - Tureniyazova, A. (SCIENCE and SOCIETY, 2022)
The paper demonstrates the effectiveness of methods for solving nonlinear equations in example of using Newton’s and Steffensen’s methods for solving level 5 equation.